Should anesthesiologists worry about climate change exposure in patients? A scoping review - Nikhila Yerabandi; Jenny H. Chang; Kimberly P. Woo; Mary Schleicher; Ilyssa O. Gordon; Benjamin T. Miller; Ursula Galway (The Journal of Climate Change and Health)
Introduction: The healthcare industry, especially anesthesia, is a significant contributor of greenhouse gas emissions; however, we do not know whether climate change affects anesthesia outcomes. Our objective was to assess the current understanding of the effects of climate change on anesthesia outcomes. Methods: We performed a comprehensive search of all literature on pediatric and adult anesthesia outcomes as a result of climate change and related extreme weather events. Results: Our search yielded 4,702 articles, out of which one met our inclusion criteria. The relevant study in our final analysis focused on adverse pediatric anesthesia outcomes after wildfire smoke exposure and found that patients with a history of reactive airway disease were at a higher risk of an adverse anesthesia outcome when exposed to unhealthy air. Conclusions: The current research on the impact of climate change on anesthesia outcomes is extremely scarce. Climate change has many effects on various organ systems, and, especially in conjunction with comorbidities, may affect anesthesia outcomes. Further research is needed to better understand perioperative complications related to climate change that can affect the health of patients requiring anesthesia.